Transient neonatal diabetes mellitus in extremely preterm infant. Issue 3 (11th January 2008) - Nishimaki, S; Yukawa, T; Makita, Y; Honda, H; Kikuchi, N; Minamisawa, S; Yokota, S
Abstract : A report of transient neonatal diabetes mellitus in an extremely preterm infant (gestational age 27 weeks, birth weight 718 g). The patient had intrauterine growth retardation and developed hyperglycaemia on the first day of life. Insulin administration was discontinued on the 89th day of life, which was 1 day before the original due date. This case suggests that ( a ) insufficient insulin secretion started at least from the second trimester of the pregnancy; ( b ) the duration needed for recovery of insulin secretion was not dependent on the maturity.